Nano-magnetic acidic and bifunctional catalyst supported on activated carbon from empty fruit bunch for biodiesel production - Ibrahim, Naeemah Abdalabbas (2020)
The critical problem arises from the fossil fuels has stimulated recent interests in alternative sources for petroleum-based fuel. An alternative fuel should be technically feasible, readily available, environment acceptable and techno-economically competitive. Biodiesel, which is considered as a potential replacement of conventional diesel fuel is commonly, composed of mono-alkyl ester of long chain that can be prepared from triglycerides which is available in renewable feedstock (vegetable oils or animal fats) utilizing transesterification technology. The feedstock used for the production of biodiesel mainly come from edible vegetable oil which is highly available in most of the countries around the world. However, the competition between food and fuel economies towards the same oil resources may bring global imbalance to the food supply and demand market. The drawbacks of homogeneous catalysts consist of corrosion to the reactor, catalyst separation difficulties, consumption of the catalyst during reaction and production of wastewater. However, conventional catalysts have strong active sites, and is cheap but the difficulty of catalyst separation from reaction is a trending issue that need to be address. To overcome the drawbacks and the limitations of heterogeneous catalysts, magnetic nanoparticle catalysts are often being utilized due to their ease of separation from products, high activity, recyclability and large surface area. This study is responsive to the concern by developing three catalysts based on nonmagnetic oxides and activated carbon (AC) to produce biodiesel from waste, feedstocks. A palm wastes of empty fruit bunches (EFB) was process to acidic fruit empty bunch (AEFB) via hydrolysis and develop into (AC). A hydrothermal reaction at 135 °C to synthesize three catalysts and were tested for biodiesel production using PFAD and WCO. In the first and second catalysts AC-Fe(10)- SO3CI and Na2SiO3-NiO-MnO/AC), the conversion of 98 and 96% were obtained while the third catalyst (CaO(10)-Fe2O3(10)/AC) the conversion was 95%. All catalysts posed excellent economic viability, since this catalyst is synthesized from waste material, high reusability (6 cycles) and posed with the most effective separation process of catalyst from biodiesel by magnetization of catalysts (AC-Fe(10)-SO3CI, Na2SiO3-NiO-MnO/AC and CaO(10)-Fe2O3(10)/AC) due to the high magnetic properties. All the catalysts were characterized to study the morphology (FESEM), functional groups (FTIR), phase and crystallize size (XRD), surface area (BET), vibrating sample magnetometer (VSM), thermal decomposition and stability (TGA) and the number and size of active sites on the surface of the catalysts (TPD-NH3). According to x-ray diffraction (XRD), the crystal size of AC-Fe(10)- SO3CI, Na2SiO3- NiO-MnO/AC and CaO(10)-Fe2O3(10)/AC catalysts were found to be 45.21, 39.64 and 32.16 nm, respectively. while the BET surface area was 36.64, 16.80 and 24.96 m2/g, respectively. TGA shows a loss of decomposition from 772°C -995°C, 289.4°C - 569.2°C and 906°C -991°C, respectively. FESEM images have shown the morphology of the surface, pore sizes, and agglomeration of the catalysts. VSM, determines the magnetization of the catalysts and shows that AC-Fe(10)-SO3CI, Na2SiO3-NiOMnO/ AC and CaO(10)-Fe2O3(10)/AC has high magnetization of 40.57, 40.27 and 85 emu/g. All three catalysts performed excellently in terms of conversion and demonstrated high magnetic separation from reaction by external magnetic field. The reusability of AC-Fe(10)-SO3CI, Na2SiO3-NiO-MnO/AC and CaO(10)-Fe2O3(10)/AC catalysts was performed for six cycles before leaching occurred and the catalysts showed high reusability with low metal leaching within the range of the EN 12662 standard specification for contamination content of diesel fuel oil. The produced biodiesel has a kinematic viscosity at 40 oC of 4.8 and 3.4, flash point of 167 and 134 for PFAD and WCO based biodiesel, respectively which were meets the standard specifications, ASTM D6751 and EN14214 standard. In conclusion, the employment of AC-Fe(10)-SO3CI, Na2SiO3-NiO-MnO/AC and CaO(10)-Fe2O3(10)/AC magnetic catalysts in esterification/transesterification reaction has significantly enhanced the catalytic activity. The activated carbon generated from agricultural waste (EFB) has demonstrated the ability to support the nonmagnetic catalysts with the display of good magnetic properties. The CaO(10)-Fe2O3(10)/AC catalyst showed the best magnetic property while the AC-Fe(10)-SO3CI catalyst showed best conversion. Potentially, these catalysts indicate the ability to be used industrially since there is the efficient catalysts separation from biodiesel section which makes the reduction of extra steps.